Myocardial injury after non-cardiac surgery: current state of the problem and unresolved issues - K. Protasov; O. Bolshedvorskaya (Российский кардиологический журнал)
The survey based  on the last decade literature,  guidelines  of international and national professional  communities  summarizes  data  on myocardial  injury after non-cardiac surgery (MINS). It reflects the growing interest in this interdisciplinary problem aroused by MINS widespread  occurrence and its close association  with after surgery mortality. Observational studies devoted to a search  for risk factors and mechanisms of after surgery myocardial injury were scrutinized. The role of asymptomatic   increase   in cardiac  troponins  which is stiffly competitive  in its clinical and prognostic  significance with after surgery  myocardial infarction was highlighted.  Modern approaches to MINS diagnostics  and  prevention  were set out.  The possibilities  and  prospects for MINS treatment were  discussed with regard  for the  results  of the  recently  completed  randomized  controlled  study MANAGE (2018). Unresolved issues  and avenues  of further investigations in the field were specified.